Perkembangan Industri Nasional dan Peran PMA - Tambunan, Tulus (Pusat Penelitian Ekonomi-LIPI, 2010)
This paper discusses about the advantages and disadvantages which happen in the national industries as a result of the domination of foreign investment. Indonesia has been losing the momentum of the development of its nation industries. From the 1970s until the 1980s , Indonesia had the opppoortunity to take control of industries in the Asian region, especially as China, Malaysia, and Thailand had still not developed their power to build and develop their industries. Without a good infrastructure and a good logistic, qualified human resources, ability to control technology which support dynamic innovational activity and intensive coorporation between universities and business world, Indonesia will be left behind by any industry from any other country. This paper result, foreign investment is important for the development of industries. Indonesia must try to absorb the advantages deriving from foreign investment. Therefore, domestic companies in Indonesia will not only become the medium but also would be able to absorb the new technology associated with foreign investment.